2012
DOI: 10.5194/nhess-12-1769-2012
|View full text |Cite
|
Sign up to set email alerts
|

The spatial structure of European wind storms as characterized by bivariate extreme-value Copulas

Abstract: Abstract.The winds associated with extra-tropical cyclones are amongst the costliest natural perils in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…This is slightly lower than the 25 ms −1 threshold used by Roberts et al (2014), in order to reduce the sampling uncertainty in locations where the wind gust speeds are weaker; therefore they rarely exceed 25 ms −1 . This threshold choice is consistent with the damage threshold used by Bonazzi et al (2012) and the damage threshold used with insurance companies in Germany as identified by Klawa and Ulbrich (2003). The SSI for windstorm event i is defined as…”
Section: Identifying a Damaging Footprint Characteristicmentioning
confidence: 68%
See 1 more Smart Citation
“…This is slightly lower than the 25 ms −1 threshold used by Roberts et al (2014), in order to reduce the sampling uncertainty in locations where the wind gust speeds are weaker; therefore they rarely exceed 25 ms −1 . This threshold choice is consistent with the damage threshold used by Bonazzi et al (2012) and the damage threshold used with insurance companies in Germany as identified by Klawa and Ulbrich (2003). The SSI for windstorm event i is defined as…”
Section: Identifying a Damaging Footprint Characteristicmentioning
confidence: 68%
“…Klawa and Ulbrich, 2003;Haylock, 2011;Bonazzi et al, 2012;Cusack, 2013;Roberts et al, 2014) or under future climate change conditions (e.g. Pinto et al, 2007Pinto et al, , 2012Leckebusch et al, 2008;Donat et al, 2011).…”
Section: Identifying a Damaging Footprint Characteristicmentioning
confidence: 99%
“…The set of 135 storms we consider contains famous European windstorm events such as 87J, Daria, Vivian, Anatol, Lothar, Martin and Kyrill. For details related to the observational data set, the storm reconstruction method and how the 135 most severe storms were selected, the reader is referred to Bonazzi et al (2012). Using the time series of the number of storms per year over the 39-year data record, we find a sample overdispersion of 1.39, strongly suggesting the time series exhibits clustering.…”
Section: A Simple Clustered Model Of European Windstorm Datamentioning
confidence: 96%
“…extreme value models (Brodin and Rootzén 2009;Della-30 Marta et al 2009), assumptions about model-dependence of simulated storms (Sansom et al 2013), and assumptions about dependency in space-time and between events (Bonazzi et al 2012;Economou et al 2014 • Numerical weather and climate models show biases in storm properties that have resisted model improvements over the past 40 years e.g. too zonal storm tracks over W. Europe , poor representation of small horizontal scale processes even at very high resolution e.g.…”
Section: Uncertainty Quantification In Windstorm Hazard Estimationmentioning
confidence: 99%